Evolution and drivers of water use in Northern China - Xiaokang Zheng; Chao Ma; Hong Lv; Fang Wan; Hao Wang (Journal of Hydrology: Regional Studies)
Study region: The 16 provinces in Northern China. Study focus: This study constructs a segmented linear regression model to identify the stages of water resource utilization and selects 11 indicators affecting changes in industrial, agricultural, and domestic water use. The logarithmic mean Divisia index (LMDI) method is applied to analyze the driving and restraining factors behind the changes in total water use in each province. New hydrological insights for the region: We identified three distinct stages of water use in Northern China: drought suppression (1997–2003), economic stimulation (2004–2012), and policy restriction (2013–2021). We selected 11 indicators affecting changes in industrial, agricultural, and domestic water use and applied the logarithmic mean Divisia index (LMDI) method to analyze the driving and constraining factors behind total water use and its variations across provinces. The results show that economic factors contributed 14 % to changes in water use, while social factors contributed 6.5 %. Additionally, the study highlights the significant role of climate change during the drought suppression phase, whereas rapid industrialization and economic growth played a dominant role in the economic stimulation phase. In contrast, policy restrictions have led to a gradual decrease in water use in recent years.